The perpetual evidence-practice gap: addressing ongoing barriers to chronic pain management in primary care in three steps - Ashcraft, Laura Ellen; Hamm, Megan E.; Omowale, Serwaa S.; Hruschak, Valerie; Miller, Elizabeth; Eack, Shaun M.; Merlin, Jessica S. (Frontiers in Pain Research, 2024)
BackgroundMost management of chronic pain, a serious illness affecting the physical and psychological wellbeing of millions, occurs in primary care settings. Primary care practitioners (PCPs) attempt to provide evidence-based practices to treat chronic pain. However, there continues to be a gap between the care people receive and the evidence. The objectives for this study were to (1) explore determinants of evidence-based chronic pain management and (2) develop a novel approach to using implementation science to address the evidence-practice gap.MethodA convenience sample of twenty-one Pennsylvania PCPs participated in one-time semi-structured telephone interviews. Interviews were transcribed verbatim and both deductive and inductive approaches were used during analysis. We used the Consolidated Framework for Implementation Research (CFIR) and the Expert Recommendations for Implementing Change (ERIC) to inform our analysis and findings.ResultsWe identified determinants of evidence-based chronic pain management across the CFIR domains of Intervention Characteristics, Characteristics of Individuals, and the Outer Setting and reported implementation strategies. Based on identified themes, we developed a three-step process to support the ongoing and pragmatic implementation of evidence-based chronic pain management in primary care settings.ConclusionsPrevious efforts exist to integrate implementation science into chronic pain management; yet a gap persists. Implementation approaches should prioritize the needs of people living with chronic pain and their families. Further, future approaches or strategies used should build on the current three-step model to include the fourth step of tailoring existing implementation strategies to the specific needs of chronic pain in the clinical context.